Spontaneous Resolution of Massive Fetal Pleural Effusion: A Case Report - Sharma, Paban; Shresta, Harihar (Nepal Journal of Obstetrics and Gynaecology, 2011)
DOI: http://dx.doi.org/10.3126/njog.v4i2.5050 NJOG 2010 Jan-Feb; 4(2): 56-58